2020
DOI: 10.1016/j.imu.2020.100392
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based drug designing towards the identification of potential anti-viral for COVID-19 by targeting endoribonuclease NSP15

Abstract: The world is facing health and economic havoc due to the Corona Virus Disease-2019 (COVID-19) pandemic. Given the number of affected people and the mortality rate, the virus is undoubtedly a serious threat to humanity. By analogy with earlier reports about Severe Acute Respiratory Syndrome (SARS-CoV) and Middle East Respiratory Syndrome (MERS-CoV) - viruses, the novel Coronavirus’ replication mechanism is likely well understood. The structure of an endoribonuclease (NSP15) of SARS-CoV-2 was reported recently. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…If the lung cell is infected with the SARS-CoV-2, preventing the virus from replicating is another treatment option [ 38 ]. Many studies have shown that miRNAs play an important role in inhibiting viruses' replication by preventing the translation of the viral genome [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…If the lung cell is infected with the SARS-CoV-2, preventing the virus from replicating is another treatment option [ 38 ]. Many studies have shown that miRNAs play an important role in inhibiting viruses' replication by preventing the translation of the viral genome [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few recent studies on the screening of Nsp15 modulators for inhibition of SARS-CoV-2 were published. Krishnan et al [ 47 ] were explored the enamine for screening against the Nsp15. They have reported promising eight molecules for the inhibition of SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…The SARS-CoV-2 protein with the top-ranked drug repurposing opportunities was Nsp15. Nsp15 is of particular interest as a drug target because it is an endoribonuclease common to all coronaviruses, is necessary for SARS-CoV-2 replication and interferes with host immune responses ( 51 , 52 , 53 , 54 , 55 , 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%